Morphological Characterization of the Testicular Cells and Seminiferous Epithelium Cycle in Six Species of Neotropical Bats - Beguelini, Mateus R. [UNESP]; Moreira, Paula R. L. [UNESP]; Faria, Karina C.; Marchesin, Sandra R. C. [UNESP]; Morielle-Versute, Eliana [UNESP] (Wiley-liss, 2009)
We know little about the process of spermatogenesis in bats, a great and diverse clade of mammals that presents different reproductive strategies. In the present study, spermatogenesis in six species of Neotropical bats was investigated by light microscopy. on the basis of chromatin condensation, nuclear morphology, relative position to the basal membrane and formation of the flagellum, three types of spermatogonia were recognized: dark type A (A(d)), pale type A (A(p)), and type B; the development of spermatids was divided into seven steps. With the exception of Myotis nigricans, the seminiferous epithelium cycle of the other five species studied was similar to those of other mammals, showing gradual stages by the tubular morphology method. Asynchrony was observed in the seminiferous epithelium cycle of M. nigricans, shown by overlapping stages and undefined cycles. The frequencies found in the three phases of the cycle were variable with the greatest frequency occurring in the postmeiotic phase (>50%) and the least in the meiotic phase (<10%). The similarities observed in the five species of Phyllostomidae appeared to be related to their phylogenetic relationship and shorter divergence times, whereas the differences in M. nigricans appeared to be related to its greater phylogenetic distance because the Vespertilionidae family diverged earlier. J. Morphol. 270:943-953, 2009.(C) 2009 Wiley-Liss, Inc.
Keywords: Spermatogenesis; Spermiogenesis; reproductive cycle; Chiroptera